Targeting the structural balance - Laura Dos Reis; Paolo Manasse; Ugo Panizza (Inter-American Development Bank, Research Department, 2007)
This paper discusses whether a country should conduct fiscal policy by targeting a structural (or cyclically adjusted) fiscal balance. The paper is divided into three sections. The first section discusses the concept of cyclically adjusted balance (CAB) and points out practical and conceptual problems related to the interpretation and the measurement of a CAB. The second section discusses the theoretical rationale for having a fiscal rule in general and a rule defined in terms of a cyclically adjusted balance in particular. The third section discusses conceptual and practical problems with adopting fiscal rules and rules that target the structural balance.
Keywords: 330